2021
DOI: 10.1182/bloodadvances.2020003763
|View full text |Cite
|
Sign up to set email alerts
|

American Society of Hematology 2021 guidelines on the use of anticoagulation for thromboprophylaxis in patients with COVID-19

Abstract: Background: Coronavirus disease 2019 (COVID-19)–related critical illness and acute illness are associated with a risk of venous thromboembolism (VTE). Objective: These evidence-based guidelines of the American Society of Hematology (ASH) are intended to support patients, clinicians, and other health care professionals in decisions about the use of anticoagulation for thromboprophylaxis for patients with COVID-19–related criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
376
3
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(416 citation statements)
references
References 84 publications
(95 reference statements)
3
376
3
15
Order By: Relevance
“…In contrast, some clinicians who were already prescribing standard dose thromboprophylaxis with LMWH (such as dalteparin 5000 IU once daily) increased the dose to an intermediate (5000 IU twice daily) or even therapeutic level (200 IU/kg). Early national and international guidance based on expert opinion has been inconsistent 891011…”
mentioning
confidence: 99%
“…In contrast, some clinicians who were already prescribing standard dose thromboprophylaxis with LMWH (such as dalteparin 5000 IU once daily) increased the dose to an intermediate (5000 IU twice daily) or even therapeutic level (200 IU/kg). Early national and international guidance based on expert opinion has been inconsistent 891011…”
mentioning
confidence: 99%
“…Effective anticoagulation is a critical area of investigation to improve outcomes in coronavirus infection. Vitamin K antagonists, including heparin, are commonly used for preventing venous thromboembolism in COVID-19, although no strong evidence yet supports any specific anticoagulant (Cuker et al, 2021). Retrospective analysis suggested that low molecular weight heparin benefits patients with signs of coagulopathy (Tang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In our population, 81% of the patients underwent anticoagulant therapy with enoxaparin. The importance of COVID-19 vascular involvement and the potential role of anticoagulant and antiplatelet drugs has been underlined in several studies [ 18 , 19 ], and at the time of writing, anticoagulants are still a cornerstone of COVID-19 treatment protocols [ 20 ].…”
Section: Discussionmentioning
confidence: 99%